Effect of amino acids (Bcaa) on some physical abilities of advanced futsal players (Journal of the College of Basic Education, 2023)
The study aimed to identify the physical capabilities, complex skills, biochemical variables and kidney functions, and to prepare a proposed training curriculum that is compatible with the capabilities of the research sample, and to determine the doses of amino acids (BCAA) that are compatible with the capabilities of the research sample.The researcher assumed that there are statistically significant differences between the results of the pre and posttests of the first and second experimental groups in some physical abilities, complex skills, and biochemistry for the research sample group. From my club and divided into two experimental groups, the first and the second experimental, with (10) players for each group, then the researcher conducted tribal tests on the research sample, and the duration of the implementation of the curriculum continued (12) weeks, distributed over (36) training units, with (3) training units in week, where the time of the training unit was (90) minutes.After completing the application of the training curriculum on the research sample, the researcher conducted post-tests on the research sample, and the results were processed statistically using the statistical bag (spss). Football for halls. Training using special exercises for compound skills has positive effects in developing the skillful and physical performance of soccer players. The researcher recommends the need to take the results of this study and benefit from them and circulate them to the competent authorities, including the beneficiary, as well as benefit from the complex skills prepared by the researcher in training futsal players,Developing standardized and high-stress training curricula when the players reach the special preparation period, because of the clear impact of these stresses on developing physical abilities and compound skills in football, and thus the coach can bring the players to the sports format.